A Review of 14 Cases of Obturator Hernia - Kodama, Masaaki; Yamazaki, Kazuma; Kondho, Satoru; Ogura, Yukiko (Nihon Fukubu Kyukyu Igakkai Zasshi (Journal of Abdominal Emergency Medicine), 2013)
(Purpose) We clinically reviewed patients with obturator hernias who were treated in our hospital. (Subjects and Methods) The subjects were 14 patients who underwent surgery in our hospital between 2000 and 2012. The mean age was 82.8 years old, and all patients were females. The mean BMI was 18.2 kg/m2. The majority of the chief complaints was vomiting or abdominal pain, and the Howship-Romberg sign was observed in 5 cases. Preoperative CT scan revealed obturator hernia in 12 patients. Preoperative duration from onset was 1-18 days. Emergency surgery was performed with the open method in all cases. (Results) Seven of the 14 patients underwent partial resection of the small intestine and the other 7 patients were saved from intestinal resection, the mean preoperative duration in whom was 4.7 days and 1.1 days, respectively. In patients with intestinal perforation, the preoperative duration was more than 3 days. The hernia hilus in 6 cases was closed with simple closure, and with artificial mesh in 6 cases. Twelve of the 14 patients were discharged or transferred to another hospital. (Conclusion) All the patients with obturator hernia were elderly females who were slender. An early CT scan should be performed for an accurate diagnosis, because early diagnosis and surgery were important to avoid intestinal resection.